2004
DOI: 10.1038/sj.leu.2403443
|View full text |Cite
|
Sign up to set email alerts
|

Response to antiviral treatment in hepatitis C virus-associated marginal zone lymphomas

Abstract: A link between chronic hepatitis C virus (HCV) infection and low-grade B-cell lymphomas has been suggested by epidemiological studies. Marginal zone lymphomas (MZLs) including splenic lymphomas with villous lymphocytes are among the most frequently reported subgroups in the setting of chronic HCV infection. In this study, we examined the effect of antiviral treatment in eight patients with HCV-associated MZL. We found that five out of eight patients have responded to interferon alpha and ribavirin. In some cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 49 publications
3
66
1
3
Order By: Relevance
“…This model has been well established in gastric MALT lymphomas, which are driven by Helicobacter pylori, as well as in maltomas with localizations other than the stomach in which various micro-organisms have been implicated; this may well be the case in at least a subgroup of SMZL patients. The hypothesis of chronic antigen stimulation as an initiating event in SMZL is supported by the fact that the disease is seen in patients with hepatitis C, and it has been shown that treatment directed to the eradication or control of this virus results in the remission of the lymphoma [10,11], and by studies on mutations of the immunoglobulin variable heavy chain (IgVH) genes that suggest a distinct and biased usage with stereotyped CDR3 sequences in some cases (see later). Splenic marginal zone lymphoma is a disease of adults without sex predominance.…”
Section: Epidemiology and Etiology Is Smzl Triggered By An Antigen?mentioning
confidence: 89%
See 1 more Smart Citation
“…This model has been well established in gastric MALT lymphomas, which are driven by Helicobacter pylori, as well as in maltomas with localizations other than the stomach in which various micro-organisms have been implicated; this may well be the case in at least a subgroup of SMZL patients. The hypothesis of chronic antigen stimulation as an initiating event in SMZL is supported by the fact that the disease is seen in patients with hepatitis C, and it has been shown that treatment directed to the eradication or control of this virus results in the remission of the lymphoma [10,11], and by studies on mutations of the immunoglobulin variable heavy chain (IgVH) genes that suggest a distinct and biased usage with stereotyped CDR3 sequences in some cases (see later). Splenic marginal zone lymphoma is a disease of adults without sex predominance.…”
Section: Epidemiology and Etiology Is Smzl Triggered By An Antigen?mentioning
confidence: 89%
“…Certainly, there is evidence that patients with hepatitis C respond to IFN-a with or without ribavirin and these agents should be considered front-line treatment in this group of patients [10,11]. In the remaining patients, splenectomy has been considered the 'gold standard' for the active management of SMZL for many years [18].…”
Section: Management and Treatment Of Smzl Early Versus Late Interventimentioning
confidence: 99%
“…In the small proportion of patients with concomitant HCV infection, interferon-a 2b (IFN), ribavirin or a combination of both these agents has demonstrated a significant activity with clearance of HCV RNA in the blood; 8,77,78 therefore, these agents should be considered in the therapeutic scenario as a first line in this small cohort of patients. A minority of patients (ca.…”
Section: Management Of Smzlmentioning
confidence: 99%
“…4,5,13,14 These notions are further strongly supported by the observation that a proportion of HCV-related MC and NHL are curable by virus eradication. [15][16][17][18][19] Conceivably, the similarity in the structure of the variable BCR region may account for selection of B cells expressing specific and common reactivity.…”
Section: Introductionmentioning
confidence: 99%